Analysis of Microwave-Assisted Heating and Water Extraction from Imidazolium and Phosphonium Based Ionic Liquids - Romero-Figueroa, J; Quijada-Maldonado, E; Torres-Mediano, A; Araya-Lopez, C (ELSEVIER, 2022)
Ionic liquids have attracted widespread attention due to their low melting points, low vapor pressure, and non-flammability. However, their application at industrial scale is uncommon due to high costs and low recovering efficiency of the ionic liquids within the process. To reduce the costs and environmental effects of ionic liquids, this study proposes to use industrial microwave irradiation to recover eight different ionic liquids from water. The heating kinetics and identification between dielectric and convective heat properties were studied. Imidazolium-based ionic liquids showed the best results, reaching higher temperatures in shorter periods of time. Ionic liquid (bis(trifluoromethylsulfonyl) trihexyl(tetradecyl) phosphonium imide ([P-6,P-6,P-6,P-14][Tf2N]) reached a temperature of 398 K in 360 s). On the other hand, the ionic liquid (1-butyl-3-methylimidazolium methylsulfate ([bmim] [CH3OSO3]) reached a temperature of 417 K in 150 s). the ionic liquid Microwave heating experiments (water/ionic liquids) demonstrated a 90% recovery in similar to 200 s for 1-octyl-3-methylimidazolium chloride ([omim][Cl]). Finally, the time used to heat-up ionic liquids with microwave irradiation was 15 times shorter than the time employed with vacuum-assisted distillation. Therefore, microwave-assisted heating has shown to be an excellent form to heat ionic liquids to decrease the cost of the extraction process and improve their reusability.